Phase Transformation of Colloidal Cs3Cu2Cl5 Nanocrystals to CsMCl (M = Zn, Bi, Cd) by Cation Exchange and Their Thermodynamic Study by Density Functional Theory Calculations - Kwon, Hyo Geun; Lee, Seung Min; Ryu, Jehyeon; Park, Ju Hyun; Kwak, Sang Kyu; Kim, Sang Wook (Chemistry of Materials, 2023)
We present the phase transformation from colloidal Cs3Cu2Cl5 nanocrystals to CsMCl (M = Zn, Bi, Cd) by cation exchange reaction. Cs2ZnCl4, Cs3BiCl6, and CsCdCl3 were successfully synthesized, and the feasibility of phase transformations was demonstrated using density functional theory calculations, which revealed the high thermodynamic stability of the three structures. The results indicate that these structures can be synthetically prepared. The difference in reactivity between Zn, Bi, and Cd cations, which was verified by changing the reaction temperatures, was demonstrated using chemical softness calculations considering the interactions between Cl- and three cations. Additionally, for each cation exchange reaction, thermodynamic stability, estimated in terms of the formation energy, contributed to reactivity. The Cs2ZnCl4 structure required the mildest reaction condition (i.e., 110 °C). As a reverse reaction, Cu cations were added to solutions of Cs2ZnCl4, Cs3BiCl6, and CsCdCl3, and CsCu2Cl3 was obtained instead of Cs3Cu2Cl5. The mechanism was not cation exchange, and transmission electron microscopy data showed that nanoparticles were used as precursors for forming CsCu2Cl3 particles.
Keywords: Cation exchange reactions; Cation exchanges; Chemical softness; Density-functional theory calculations; Formation energies; Phases transformation; Reaction temperature; Reaction thermodynamics; Synthesised; Thermodynamic studies